Effects of oral, oronasal, and oronasal breathing with a decongested nose during incremental maximal exercise testing of well-trained endurance athletes: a randomized cross-over study - Bergqvist, J.; Reite, F.; Edin, F.; Schiöler, L.; Börjesson, M.; Steinsvåg, S.; Pettersson, S.; Hellgren, J. (Frontiers in Physiology, 2025)
Introduction: Nasal breathing is preferable for persons at rest and remains partially active during oronasal breathing in exercise. However, its potential contribution to performance-particularly in cases with a decongested nose-remains understudied in well-trained athletes. This study investigates whether nasal airflow during oronasal breathing influences performance in well-trained, endurance athletes. Specifically, we examine whether nasal decongestion during oronasal breathing enhances ventilatory efficiency and, thereby, improves time-to-exhaustion (TTE), maximal oxygen uptake (VO2max), and maximum power output (Wmax), as compared to oral-only breathing.